Mean Platelet Volume in Patients With Subclinical Hypothyroidism Attending at A Tertiary Care Hospital of Bangladesh (Journal of Dhaka Medical College, 2023)
Background: Subclinical hypothyroidism (SCH) is a common endocrine disorder affecting about 3-8% of the general population. On the other hand, mean platelet volume (MPV) is an indicator of platelet activity, and elevated MPV is associated with adverse cardio-metabolic complications. This study was conducted to observe MPV in SCH and to correlate it with thyroid-stimulating hormone (TSH) and free thyroxine (FT4) levels.Materials and Methods: This cross-sectional observational study was conducted in Medicine and Endocrinology OPD of US- Bangla Medical College & Hospital over twelve (12) months from September 2020 to August 2021. This study included forty (40) cases of newly detected SCH and twenty (20) age & body mass index (BMI) matched euthyroid control subjects as per inclusion and exclusion criteria.Results: SCH group had higher TSH and MPV than controls (P value